面向UG的差速器CAD系统开发 - 郑泉; 陈黎卿; 何钦章 (Jixie chuandong)
A design system for differential gear parametrization is realized in UG and Visual C + +. The key technologies of building the three dimensional model with UG OPEN is discussed in detail. The differential gear CAD system has carried on the confirmation through the concrete example. Compared with the traditional design method, this method increased design precision and efficiency.